Mossbauer spectra of Fe3+-poor schorls: reinterpretation on the basis of the ordered structure model - Pieczka,A.; Kraczka,J.; Zabinski,W. (Journal of the Czech Geological Society, 1998)
Mossbauer spectra of tourmalines are usually interpreted assuming a disordered distribution of octahedral ions, particularly of Fe2+ and Al3+, between Y and Z structural sites (Hermon et al. 1973, Korovushkin et al. 1979, Ferrow et al. 1988). Sometimes, as it is in the case of Fe-elbaites, such assumptions are baseless on the ground of crystallochemistry. The analyses of statistical relationships between mean bond lengths and cation populations of Y and Z octahedra of tourmalines with Al > 6 apfu have shown a significant effect of ionic substitutions in neighbouring cation sites (particularly within the triad of the Y octahedra) on the mean sizes of both structural sites. As a result, disordering of octahedral ions may have much lesser significance or be completely absent. The paper presents a possibility of crystallochemical interpretation of quadrupole splitting doublets in the Mossbauer spectra of Fe3+-poor schorls. The proposed interpretation is based on an analysis of frequency of Fe2+ occurrences within particular ion groups in the Ist and and IInd coordination shells. If Fe2+ occurs as a central ion in Y octahedra, the O(3) site is occupied by (OH)-, and differences in the Ist coordination shell result from substitution of (OH-, F-, O2-) ions in the O(1) site. In the IInd coordination shell, the variability of ions is basically limited to cations of the remaining two Y octahedra. Groups of ions, which may occur around Fe2+, have eventually been arranged into five sets of different variants, revealing crystallochemical similarity within each set and, as it can be supposed, affecting the Fe2+ ion in the same way. The results are characterized by very good occurrence of spectroscopic and chemical data, i.e. the contribution of quadrupole splitting doublets of Fe2+ ions to a whole spectrum and calculated shares of Fe2+ in specific groups of ions of the Ist and IInd coordination shells related to total Fe. By the same virtue, the presence of numerous doublets of quadrupole splitting in the Mossbauer spectra of tourmalines can be fully explained on a basis of crystallochemical properties, without assuming a random distribution of octahedral ions.
Keywords: tourmaline; schorl; Mossbauer spectrum; crystallochemical interpretation; the ordered structure model